2014
DOI: 10.1098/rstb.2013.0435
|View full text |Cite
|
Sign up to set email alerts
|

The coverage and frequency of mass drug administration required to eliminate persistent transmission of soil-transmitted helminths

Abstract: A combination of methods, including mathematical model construction, demographic plus epidemiological data analysis and parameter estimation, are used to examine whether mass drug administration (MDA) alone can eliminate the transmission of soil-transmitted helminths (STHs). Numerical analyses suggest that in all but low transmission settings (as defined by the magnitude of the basic reproductive number, R0), the treatment of pre-school-aged children (pre-SAC) and school-aged children (SAC) is unlikely to driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
205
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(215 citation statements)
references
References 31 publications
9
205
1
Order By: Relevance
“…Mathematical modeling studies recently suggested that, in such settings, community MDA and more frequent treatments are more likely to achieve a significant impact (and possibly, interrupt transmission of STHs) than programs using selective MDA for school children only on an annual basis. 26,27 Our preliminary results tend to support the modelers' predictions. In Seke Pembe, the first two rounds of MDA with ALB at high coverage had a significant impact on STH infection levels, with increasing effectiveness for T. trichiura, A. lumbricoides, and hookworm.…”
Section: Discussionsupporting
confidence: 76%
“…Mathematical modeling studies recently suggested that, in such settings, community MDA and more frequent treatments are more likely to achieve a significant impact (and possibly, interrupt transmission of STHs) than programs using selective MDA for school children only on an annual basis. 26,27 Our preliminary results tend to support the modelers' predictions. In Seke Pembe, the first two rounds of MDA with ALB at high coverage had a significant impact on STH infection levels, with increasing effectiveness for T. trichiura, A. lumbricoides, and hookworm.…”
Section: Discussionsupporting
confidence: 76%
“…This is especially true in communities where hookworm is the predominant infection, as prevalence of hookworm infection peaks in adulthood [30]. Modeling of STH transmission under repeated rounds of MDA suggests that due to continued transmission at the community level, PSAC-targeted and SAC-targeted deworming programs will need to continue indefinitely -or at least until economic development, access to adequate water and sanitation, and other sociodemographic changes occur -to maintain benefit [10,31].…”
Section: The Case For Community-wide Mass Drug Administration For Soimentioning
confidence: 99%
“…Models (and some empiric data) suggest that transmission interruption may be possible through chemotherapy alone, provided that the treated population is expanded to all age groups and high coverage is achieved [8][9][10]31,33,34]. Experience from the Global Alliance to Eliminate Lymphatic Filariasis, which provides community-wide MDA with a package of drugs, including albendazole, has demonstrated that achieving high treatment coverage through community delivery of MDA is possible [35].…”
Section: The Case For Community-wide Mass Drug Administration For Soimentioning
confidence: 99%
See 1 more Smart Citation
“…These are drugs for bacterial [9] and helminth infections [10,11], vaccines for pathogens of all kinds [12], and insecticides [13] and the manipulation of heritable characteristics for mosquito control [14].…”
mentioning
confidence: 99%